2019
DOI: 10.1111/bjet.12774
|View full text |Cite
|
Sign up to set email alerts
|

Professional ecologies shaping technology adoption in early childhood education with multilingual children

Abstract: Strategic deployment of the digital world in educational ecosystems inhabited by multilingual children (4–6 years old), their teachers and their families is evolving in some communities. This study reveals the “actors” and communities that mediate the extent and the nature of engagement with new media in contexts of early childhood education, including evidence of partnership with teachers. Teachers and parents were found to be the “keystone species,” with the teacher the most influential mediator for young mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
0
9
0
2
Order By: Relevance
“…Bond’s study warns against optimism in this respect: observing that family engagement will not be cultivated by any such simple mediation of technology. Davis, Harris and Cunningham () also considers parents and offers a more fully articulated ecological analysis of educational practice, drawing upon the example of language learning. Here, there is a useful effort to integrate the material and digital environments: one which demonstrates how a hesitant adoption of technology may be understood in terms of the dynamics that arise within them.…”
Section: The Micro‐layermentioning
confidence: 99%
See 1 more Smart Citation
“…Bond’s study warns against optimism in this respect: observing that family engagement will not be cultivated by any such simple mediation of technology. Davis, Harris and Cunningham () also considers parents and offers a more fully articulated ecological analysis of educational practice, drawing upon the example of language learning. Here, there is a useful effort to integrate the material and digital environments: one which demonstrates how a hesitant adoption of technology may be understood in terms of the dynamics that arise within them.…”
Section: The Micro‐layermentioning
confidence: 99%
“…An ecological perspective involves awareness of the rich variety of settings within which educational practice takes place: accordingly, research will need to confront this variety, to capture and express it. For example, from the corpus of research reported in this Special Issue, there is clearly a significant gulf between “a Chinese middle‐high boarding school” (Sun & Gao, ) and a primary school in a culturally diverse area of New Zealand (Davis et al , ). Yet we should retain faith in the central place of the findings from such case studies.…”
Section: Moving Forwardmentioning
confidence: 99%
“…Although the digital disconnect between home and school exists, it is more important to understand why some technologies are used at home or in early years settings and how that choice is mediated by the different socio‐ecological settings (Edwards et al., 2017). Looking at the views of the responsible adult/s in both settings is important since teachers and parents are the keystone species setting up mediation of the digital world to benefit and protect young children (Davis et al., 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in her ecological approach, Davis () offered a model for the take‐up of ICT in which the classroom was nested within a school, district, state, national and global ecology. This was further developed in an “arena framework” (Davis et al ., ) which used a more ecological science vocabulary: teachers work in eco systems , blends of physical and digital worlds; species are introduced to systems; the teacher is the keystone species in the educational system (the one with proportionally the largest effect, albeit highly influenced by organisational culture). A similar ecological metaphor appears in Zhao et al () in which technology itself is a “species” introduced into school.…”
Section: How To Apply An Ecological Approach To Researching Ict Take‐upmentioning
confidence: 99%
“…This paper argues for an ecological perspective when researching the take‐up of ICT in schools. There has been increasing interest in ecological approaches and ecological metaphors in considering teacher adoption of ICT (eg, Davis, Harris, & Cunningham, ; Johnson & Puplampu, ; Kozma, ; Law, Kampylis, & Punie, ; Nardi & O’Day, ; Slaouti & Barton, ; Zhao, Lei, & Frank, ), but on‐going tensions persist in the way an ecological approach is understood. The aim of this paper is to clarify what an ecological approach consists of and to show how such an approach can help to explain levels of ICT take‐up.…”
Section: Introductionmentioning
confidence: 99%